TARC/CCL17 reflects the severity of pemphigus (pemphigus vulgaris and pemphigus foliaceus) at the initial presentation - Tomoya Takegami; Satoru Yonekura; Takashi Nomura; Gyohei Egawa; Kenji Kabashima (Wiley, 2024)
Abstract Background Pemphigus vulgaris (PV) and pemphigus foliaceus (PF) are autoimmune blistering diseases targeting desmoglein 3 (Dsg3) or desmoglein 1 (Dsg1). The current scoring system, pemphigus disease area index (PDAI), has limitations including inter‐ and intra‐evaluator variability, as well as a time‐consuming evaluation process. Objectives To identify objective and quantitative surrogate markers for assessing disease severity in PV and PF. Methods Eleven PV and PF patients were included. PDAI scores and candidate biomarkers [anti‐Dsg3 antibody, anti‐Dsg1 antibody, thymus and activation‐regulated chemokine (TARC)/CCL17, immunoglobulin E (IgE) levels and eosinophil counts] were measured before oral corticosteroid treatment. Pearson's correlation coefficient was used for correlations between PDAI and candidate biomarkers. Results Serum TARC/CCL17 levels significantly correlated with PDAI scores in PV and PF (R = 0.72, p = 0.02), while anti‐Dsg3 antibody levels correlated with PDAI scores for PV (R = 0.86, p = 0.012). No significant correlations were observed for anti‐Dsg1 antibody, eosinophil counts or IgE levels. Conclusions Serum TARC/CCL17 may be a quantitative and unbiased disease biomarker in pemphigus patients, although further studies involving larger patient cohorts are needed.